Sexual constitution and endothelial function of the cavernous arteries in men with erectile dysfunction - ASHURMETOV, Azizbek Mirsagatovich (International Journal of Psychosocial Rehabilitation, 2020)
to evaluate the frequency of endothelial dysfunction of the cavernous arteries, the prevailing type of sexual constitution in men with cardiovascular diseases and risk factors.Eighty-three men aged from 32 to 74 years old with cardiovascular diseases (or CVD) and cardiovascular risk factors were examined. All men underwent a comprehensive examination. In addition, a questionnaire survey was conducted on the ICEF-5 (or International Index of Erectile Function) and on the scale of the vector definition scale of men sexual constitution, the genotypic index (or Kg), phenotypic index (or Kf), and a constitutionally modeled index of sexual constitution (or Ka) were calculated. All patients underwent an original method for studying the endothelial function of the cavernous arteries using ultrasound dopplerography after exposure to infra-red emitter.manifestations of erectile dysfunction (ED) were detected in 79 (95.2%) patients. In 77.1% of men with ED, the vector of sexual constitution was within the middle and weakened middle variants. A correlation was found between the presence of ED and the genotypic index (g = 0.48; p = 0.001), as well as between the presence of ED and the phenotypic index (g = 0.42; p = 0.001). In the study of the endothelial function of the cavernous arteries, endothelial dysfunction was detected in 79 (95.2%) patients. In 60 (75.9%) patients, paradoxical vasoconstriction was determined.a weak and weakened version of the average sexual constitution is a predictor of endothelial dysfunction and erectile dysfunction. The obtained results confirm the need for active attention and inclusion in the survey standards of determining the vector of the sexual constitution of men with ED.